Endothelial Dysfunction in Fabry Disease Is Related to Glycocalyx Degradation - Pollmann, Solvey; Scharnetzki, David; Manikowski, Dominique; Lenders, Malte; Brand, Eva (Frontiers in Immunology, 2021)
Fabry disease (FD) is an X-linked multisystemic lysosomal storage disease due to a deficiency of α-galactosidase A (GLA/AGAL). Progressive cellular accumulation of the AGAL substrate globotriaosylceramide (Gb3) leads to endothelial dysfunction. Here, we analyzed endothelial function in vivo and in vitro in an AGAL-deficient genetic background to identify the processes underlying this small vessel disease. Arterial stiffness and endothelial function was prospectively measured in five males carrying GLA variants (control) and 22 FD patients under therapy. AGAL-deficient endothelial cells (EA.hy926) and monocytes (THP1) were used to analyze endothelial glycocalyx structure, function, and underlying inflammatory signals. Glycocalyx thickness and small vessel function improved significantly over time (p<0.05) in patients treated with enzyme replacement therapy (ERT, n=16) and chaperones (n=6). AGAL-deficient endothelial cells showed reduced glycocalyx and increased monocyte adhesion (p<0.05). In addition, increased expression of angiopoietin 2, heparanase and NF-κB was detected (all p<0.05). Incubation of wild-type endothelial cells with pathological globotriaosylsphingosine concentrations resulted in comparable findings. Treatment of AGAL-deficient cells with recombinant AGAL (p<0.01), heparin (p<0.01), anti-inflammatory (p<0.001) and antioxidant drugs (p<0.05), and a specific inhibitor (razuprotafib) of angiopoietin-1 receptor (TIE2) (p<0.05) improved glycocalyx structure and endothelial function in vitro. We conclude that chronic inflammation, including the release of heparanases, appears to be responsible for the degradation of the endothelial glycocalyx and may explain the endothelial dysfunction in FD. This process is partially reversible by FD-specific and anti-inflammatory treatment, such as targeted protective TIE2 treatment.